ANALISIS VEGETASI TUMBUHAN LIANA DI GUNUNG SIBUATAN DESA NAGALINGGA KECAMATAN MEREK KABUPATEN KARO SUMATERA UTARA - Edty Widya Ningsih Harahap; Kartika Manalu; Melfa Aisyah Hutasuhut (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2021)
Lianas are a unique group of climbing plant species that are characteristic of tropical rainforests. This species has important ecological and economic value. This study aims to find out information about the composition and structure and diversity index of lianas. The research method used is a quadratic method with 10 plots laid out by purposive sampling. The results showed that the composition of lianas consisted of 22 families, 31 species and 414 individuals. The highest Importance Value Index in Amydrium humile Schott (INP 23, 145%), where as liana species with the lowest of Value index was Stephania sp. (INP 2, 343%). The diversity index of lianas is in the medium category, with the H’ 2.965.